Nur al-Din Zangi and his Relations with Ayyubid Family - Ari Kakil Mohmedtaher; Abdulkhalq othman (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The rise of the two Families, Ayyubid and Zangi, made an important period in Islamic History after coming into view great leaders like Imad ad-Din Zengi and his son Nur al-Din, Salahaddin Ayyubi and others who couldrestore Islamic prestige after suffering a lot from political disconnection, By their efforts unity of Muslims had been achierved. The two families led resistance movements and Jihad against Crusaders, they could attain great Victories as a resuit of these leaders political and intellectual maturity, consciousness and loyalty to Islam, they struggled under one flag. The study is an attempt to deal with the connections between the two families since the reign of sultan Imad ad-Din Zengi Mahmood there is no doubt, the strong ties between the two families played asignificant role in Unifying Muslims and had its effects upon the wars against their enemy: Crusaders, This strong relation affected economic, social and cultural activities as well.